MINERALS AND FORMATION CONDITIONS OF ORES OF THE TEREMKIN GOLD DEPOSIT (EASTERN TRANSBAIKAL REGION, RUSSIA) - Prokof'ev V.Yu.; Plotinskaya O.Yu.; Zorina L.D.; Baksheev I.A.; Kudryavtseva O.E.; Ishkov Yu.M. (My University, 2004)
Physicochemical conditions of the formation of ores from the Teremkin gold deposit have been reconstructed on the basis of comprehensive studies of fluid inclusions and chemical compositions of principal minerals of ore veins: tourmaline, mica, carbonate, gold, sphalerite, and galena. The hydrothermal process at the Teremkin deposit was established to proceed at temperatures of 466... 118°C and pressures of 410... 70 bar on the background of a heterogeneous state of the ore-forming fluids and elevated oxidizing potential at the beginning of the hydrothermal process. Productive mineralization formed at temperatures of 297...216°C and pressures of 160...70 bar. The concentration of salts in fluids varied from 34.7 to 1.2 wt %-equiv. NaCl. Basic fluid components are represented by sodium and calcium chlorides, carbon dioxide, and boron. High concentrations of boron in ore-forming fluid of the Teremkin deposit and values of the ratios K/Rb, Sr/Rb, Ba/Rb, Sr/Ba, and Ni/Co in the fluid of inclusions indicate its magmatic nature and the magmatic source of some elements in ores. Physicochemical parameters of the formation of the object of study have been compared to those of the Darasun deposit. The small scale of gold mineralization at the Teremkin deposit is accounted for, first of all, by a short-term ore-forming process.